Peran Media Sosial sebagai Sarana Penginjilan Efektif dalam Menjangkau Jiwa-Jiwa - Nurlela Syafrian Oematan; Lucky Antonio; Matius Kala'tiku; Anita Mariana Parulian Butar-Butar; Chanita Christie (REDOMINATE Jurnal Teologi dan Pendidikan Kristiani, 2023)
The role of social media as an effective means of evangelism in reaching souls around us. With the development of technology and the high use of social media among the community, this media platform has become a strategic tool for evangelists to spread the message of faith. This Media Role study analyzes various methods and content used in digital evangelism. Through a qualitative approach, data was collected from interviews, surveys, and content analysis published on social media. The results of the study indicate that social media not only expands the reach of evangelism, but also facilitates more personal and in-depth interactions with individuals. Thus, social media has proven to be a very useful innovative tool. Evangelization efforts, which can overcome geographical and cultural boundaries, and respond to the spiritual needs of modern society.